"The Name Says It All, It's Saraybostan": Low-Income Kurdish Migrant Women's Experiences with Life in a Poverty-Impacted Urban Neighborhood. Issue 6 (2nd November 2017) - Sensoy Bahar, Ozge
ABSTRACT: As part of a larger ethnographic study on low-income Kurdish mothers' reconstruction of their lives after rural-to-urban migration, this article explored how they experienced life in a poverty-impacted neighborhood of Istanbul, Turkey. Twenty-seven Kurdish mothers were recruited through purposive and snowball sampling. Data were collected through demographic surveys, semi-structured in-depth interviews, and participant observations. Women's narratives focused primarily on three aspects, namely financial challenges, crime, and neighbor relations. Participants discussed both challenges and coping strategies pertaining to each aspect. Study findings underlined similarities and differences in life experiences of families living in poverty-impacted urban communities across the global context.